Analisa Perencanaan Kebutuhan Material pada Perusahaan Manufaktur Kertas dengan Metode Material Requirement Planning (MRP) - Lestari, Sri; Nurdiansah, Distian Dwi (Universitas Serang Raya, 2018)
The development of the business world is currently experiencing a very rapid growth rate. Planning for the proper procurement of materials will be able to facilitate the company's production activities. Production process activities in companies often experience problems such as inaccurate production, which is caused by delays in the arrival of raw materials, and damage to raw materials due to too long storing in warehouses. This study aims to plan future needs with the Material Requirement Planning (MRP) approach by doing forecasting, making the Master Production Schedule (MPS), Material Requirement Planning (MRP) and conducting a cost analysis of the five methods used. The results of this study are forecasting product demand will be used linear regression method, and effective material requirements planning method with the lowest cost is to use the Lot For Lot (LFL) method of 164.48. The application of the Lot For Lot method can reduce costs by 90.06% compared to the Fixed Period Requirements (FPR) method used by the company.